PENGARUH MODEL PEMBELAJARAN OE (OPEN ENDED) BERBASIS MULTIMEDIA INTERAKTIF TERHADAP PRESTASI BELAJAR MATA PELAJARAN TIK PADASISWA KELAS VIII SMPN SATAP 1 KAYANGAN - Nurman Nurman; Hadi Gunawan Sakti (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2017)
Abstract: The Open Ended Learning Model is a problem-solving process that prioritizes the process rather than the product that will shape the mindset of integration, openness, and diversity of thinking equipped with an interactive multimedia blend as the innovation color in learning. While Learning Achievement is a change in behavior that occurs after following the teaching and learning process in accordance with the purpose of education. Based on the results of field studies that have been conducted researchers, student achievement is less this is influenced by teachers are less creative in choosing a model of learning so that students' motivation is less in learning. The problem in the research is whether there is Influence Learning Model OE (Open Ended) Based Interactive Multimedia Against Student Achievement Subjects Class ICT Class VIII SMPN Satap 1 Kayangan KLU Lesson 2015/2016? The objectives to be achieved in this study is the influence of learning model OE (Open Ended) Based Interactive Multimedia Against Student Achievement Subjects Class ICT Class VIII SMPN Satap 1 Kayangan KLU Lesson 2015/2016. Subjects in this study by using One Group Sampling counted 37 people. The method used in this research is the test method as the main method, while the observation, interview and documentation as complementary method. Data analysis using the formula-test. Based on the results of data analysis with 5% significance level, then obtained the result of research that is tcount value bigger than ttable value (t-hitung 7,604> t-table 2,021). Then it can be concluded that Ho is rejected while Ha is accepted. Thus the hypothesis (Ha) reads: There is the Influence of Learning Model OE (Open Ended) Based Interactive Multimedia Against Student Achievement Subject Class ICT Class VIII SMPN Satap 1 Kayangan KLU Lesson 2015/2016 received.